Determinants of Final Project Commercialization among Movies and Art Students: Moderating Impact of Socioeconomic and Education Disparities - Lanxin; Zainudin, Zaheril Bin (South Asian Journal of Social Sciences and Humanities, 2024)
Background and Purpose: This research has designed the main objective to elucidate the role of  different commercialization capabilities (competitive intelligence capabilities, knowledge  management capabilities and quality management capabilities) in predicting the creative ideation  of art and movie students. Additionally, the moderating impact of socioeconomic status and  education disparities is also considered in the conceptual framework. Methodology: This study  was conducted within the context of China and the art and movies students were assessed using  random sampling. A self-structured questionnaire was distributed and quantitative data through  closed-ended questions was gathered from the target population. The main analysis technique was  the Partial Least Square Structural Equational Modelling PLS-SEM in the Smart PLS application. Findings: With the bootstrapping method, the analysis results depicted the significant and positive  influence of commercialization capabilities (including competitive intelligence capabilities,  knowledge management capabilities and quality management capabilities) and creative ideation  among the art students. Conclusion and Implications: The education disparities suggested a  significant external role in influencing the association between commercialization capabilities and  creative ideation. With these findings, this study has made a novel contribution to the knowledge  field by sharing the perceptions of art and movie students and enlightening their reflections  regarding the commercialization of their projects and subjective hard work.
Keywords: Commercialization capabilities; Creative ideation; Socioeconomic factors; educational disparities; China